The Mira–Titan Universe – IV. High-precision power spectrum emulation. Issue 3 (9th December 2022) - Moran, Kelly R; Heitmann, Katrin; Lawrence, Earl; Habib, Salman; Bingham, Derek; Upadhye, Amol; Kwan, Juliana; Higdon, David; Payne, Richard
ABSTRACT: Modern cosmological surveys are delivering data sets characterized by unprecedented quality and statistical completeness; this trend is expected to continue in the future as new ground- and space-based surveys come online. In order to maximally extract cosmological information from these observations, matching theoretical predictions are needed. At low redshifts, the surveys probe the non-linear regime of structure formation where cosmological simulations are the primary means of obtaining the required information. The computational cost of sufficiently resolved large-volume simulations makes it prohibitive to run very large ensembles. Nevertheless, precision emulators built on a tractable number of high-quality simulations can be used to build very fast prediction schemes to enable a variety of cosmological inference studies. We have recently introduced the Mira–Titan Universe simulation suite designed to construct emulators for a range of cosmological probes. This gravity-only set of simulations covers the standard six cosmological parameters ωm, ωb, σ8, h, n s, w 0 and, in addition, includes massive neutrinos and a dynamical dark energy equation of state ων, w a . In this paper, we present the final emulator for the matter power spectrum based on 111 cosmological simulations, each covering a (2.1 Gpc) 3 volume and evolving 3200 3 particles. An additional set of 1776 lower resolution simulations and TimeRG perturbation theory results for the power spectrum are used to cover scales straddling the linear to mildly non-linear regimes (maximum wavenumber k = 5 Mpc −1 ). The emulator provides predictions at the 2–3 per cent level of accuracy over a wide range of cosmological parameters and is publicly released as part of this paper.